Hubungan Antara Keberfungsian Keluarga Dengan Self-Regulated Learning Pada Siswa Yang Tinggal Di Asrama - Gunawan, Benedictus Aditya; Setianingrum, Margaretta Erna (Faculty of Psychology Universitas 17 Agustus 1945 Surabaya, 2018)
AbstractThis research aimed at knowing positive relationship between family functioning with self-regulated learning of Pangudi Luhur Van Lith Muntilan Senior High School students. This research was conducted on 80 students by using random sampling technique. The method used in this research is quantitative method. Measuring instrument used for family functioning is The McMaster Model of Family Functioning with alpha cronbach’s coefficient is 0,927 and self-regulated scale with alpha cronbach’s coefficient is 0,899. From the data analysis obtained the result of coefficient correlation is 0,366 with the significance amount 0,000 (p < 0,05), so it can be concluded that there is a positive correlation between family functioning and self-regulated learning of Pangudi Luhur Van Lith Muntilan Senior High School students, so the hypothesis pruposed in this study is accepted.Keywords: Family Functioning, Self-Regulated Learning Abstrak Penelitian ini bertujuan untuk mengetahui hubungan antara keberfungsian keluarga dengan self-regulated learning pada siswa di SMA Pangudi Luhur Van Lith Muntilan. Penelitian ini dilakukan pada 80 siswa dengan menggunakan teknik random sampling. Metode penelitian yang digunakan dalam penelitian ini adalah metode kuantitatif. Alat ukur yang digunakan untuk skala keberfungsian keluarga adalah The McMaster Model of Family Functioning dengan koefisien alpha cronbach sebesar 0,927 dan alat ukur skala self-regulated learning adalah The Motivated Strategies of Learning Questionnaire dengan koefisien alpha cronbach sebesar 0,899. Dari analisis data diperoleh hasil koefisien korelasi sebesar 0,366 dengan signifikansi 0,000 (p < 0,05), sehingga dapat disimpulkan bahwa ada hubungan positif signifikan antara keberfungsian keluarga dengan self-regulated learning pada siswa di SMA Pangudi Luhur Van Lith Muntilan, sehingga hipotesis yang diajukan dalam penelitian ini diterima.Kata Kunci: Keberfungsian Keluarga, Self-Regulated Learning